NT

Cho \(\left(x+\sqrt{x^2+2010}\right)\left(y+\sqrt{y^2+2010}\right)=2010\)

Tính S=x+y

VH
15 tháng 5 2017 lúc 23:07

theo đề bài \(\left(x+\sqrt{x^2+2010}\right)\left(y+\sqrt{y^2+2010}\right)=2010\)

\(\left(\sqrt{x^2+2010}+x\right)\left(\sqrt{x^2+2010}-x\right)=2010\)

nên \(\sqrt{x^2+2010}-x=\sqrt{y^2+2010}+y\)

hay \(x+y=\sqrt{x^2+2010}-\sqrt{y^2+2010}\) (1)

Tương tự \(\left(\sqrt{y^2+2010}+y\right)\left(\sqrt{y^2+2010}-y\right)=2010\)

nên \(\sqrt{x^2+2010}+x=\sqrt{y^2+2010}-y\)

hay \(x+y=\sqrt{y^2+2010}-\sqrt{x^2+2010}\) (2)

Từ (1) và (2) suy ra S = x + y = 0.

Bình luận (0)

Các câu hỏi tương tự
H24
Xem chi tiết
ND
Xem chi tiết
TD
Xem chi tiết
NV
Xem chi tiết
LS
Xem chi tiết
VC
Xem chi tiết
GN
Xem chi tiết
NH
Xem chi tiết
NC
Xem chi tiết